(untitled) (Medical Forum Monthly, 2024)
ABSTRACT Objective: To compare the frequency of inter-appointment endodontic flare-ups in controlled diabetes mellitus patients with uncontrolled diabetic mellitus. Study Design: Cross sectional comparative study Place and Duration of Study: This study was conducted at the OPD of the 28th Military Dental Centre (MDC) from 01 Jan 2016 to 01 Jan 2018. Materials and Methods: Thirty patients with controlled glucose profile and 30 uncontrolled patients were included in the study. After initiation of root canal treatment, they were recalled after the first 24 hours to assess pain. Results: It was observed that 24(80%) uncontrolled diabetic patients exhibited evidence of symptomatic apical periodontitis because of inter-appointment pain as compared to 09(30%) controlled diabetic patients. Conclusion: Incidence of inter-appointment pain was significantly much higher in uncontrolled diabetics as compared to controlled diabetic patients (p-value 0.00). Showing a probable relationship between inter- appointment pain and uncontrolled diabetes.